eCM 2017
DOI: 10.22203/ecm.v034a13
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of the chondrogenic phase of endochondral ossification in vivo by inhibition of cyclooxygenase-2

Abstract: Many studies have reported on the effects of cyclooxygenase-2 (COX-2) inhibition on osteogenesis. However, far less is known about the effects of COX-2 inhibition on chondrogenic differentiation. Previous studies conducted by our group show that COX-2 inhibition influences in vitro chondrogenic differentiation. Importantly, this might have consequences on endochondral ossification processes occurring in vivo, such as bone fracture healing, growth plate development and ectopic generation of cartilage. The goal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 23 publications
2
17
0
1
Order By: Relevance
“…Moreover, patients suffering from inflammatory disorders like rheumatoid arthritis (RA) often exhibit delayed fracture healing [2][3][4][5][6][7][8][9][10], or even develop pseudarthrosis [8][9][10]. Additionally, glucocorticoids (GCs) and nonsteroidal anti-inflammatory drugs (NSAIDs), both being in daily clinical use for the treatment of RA, have been reported to hamper bone metabolism and fracture healing [11][12][13][14][15]. Another potent therapeutic agent in the treatment of RA is the anti-inflammatory drug tofacitinib [16].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, patients suffering from inflammatory disorders like rheumatoid arthritis (RA) often exhibit delayed fracture healing [2][3][4][5][6][7][8][9][10], or even develop pseudarthrosis [8][9][10]. Additionally, glucocorticoids (GCs) and nonsteroidal anti-inflammatory drugs (NSAIDs), both being in daily clinical use for the treatment of RA, have been reported to hamper bone metabolism and fracture healing [11][12][13][14][15]. Another potent therapeutic agent in the treatment of RA is the anti-inflammatory drug tofacitinib [16].…”
Section: Introductionmentioning
confidence: 99%
“…27 However, other studies have shown deregulation of growth plate development by other NSAIDs. 11,24,[28][29][30] This study is the first to show that naproxen (in an equivalent human dosage) influences murine growth plate development, the bone microstructure, cortical bone quality, and tibial and femoral bone length.…”
Section: Altered Bone Characteristics In Naproxen-and Mtx-treated Micementioning
confidence: 77%
“…Our previous studies 11,14,24 determined that COX enzyme activity is involved in regulating the chondrogenic phase of endochondral ossification. Clinically, this is relevant as inhibition of COX enzymes by NSAIDs can result in hampered endochondral ossification.…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated and corrected for potential dropout, and eight animals per group were included. The IVB method described by Emans and colleagues was used for ectopically inducing cartilage formation, in which a subperiosteal space is created to induce periosteal endochondral ossification (Emans et al, 2007(Emans et al, , 2010Janssen et al, 2017). In short, the skin was opened over the upper medial side of the tibia, the periosteum was incised just medially of the pes anserinus, leaving the semitendinosus tendon untouched.…”
Section: Animal Studymentioning
confidence: 99%
“…We next determined if Aggrecan or COMP supplementation to the IVB biogel leads is beneficial for the quality of ectopically generated cartilage in the IVB. We used the IVB technique as described earlier (Emans et al, 2010;Janssen et al, 2017) and added either Aggrecan (2% w/v; n = 8 IVBs) or COMP (0.5 mg/ml; n = 8 IVBs) to the agarose biogel, and compared the quality of the cartilage that was generated 14 days after creation of the IVBs with a control group in which only the empty agarose biogel condition was tested (n = 8 IVBs). The wet weight of the formed IVB tissues was not significantly different between the empty agarose group versus the IVBs in which the biogel was supplemented with Aggrecan or COMP ( Figure 3A).…”
Section: Quality Of Ivb Cartilage Generated With Aggrecan or Comp Supmentioning
confidence: 99%